Blood biochemical landscape and new insights into clinical decision-making for polycystic ovary syndrome in Chinese women: a prospective cohort study - Li, Yutong; Lin, Xiufeng; Zou, Ke; Du, Jing; Li, Qingni; Zhong, Linkun; Jiang, Shan (Frontiers in Endocrinology, 2025)
IntroductionThe Polycystic ovary syndrome (PCOS), a prevalent endocrine disorder affecting women’s reproductive and metabolic health, faces diagnostic challenges due to heterogeneous clinical presentations and the absence of reliable biomarkers. This study investigates the role of Glucosaminyl (N-acetyl) transferase 2 (GCNT2) in modulating sex hormone-binding globulin (SHBG) and its potential as a therapeutic target in PCOS pathophysiology.MethodsA prospective cohort of 103 PCOS patients treated with oral contraceptives (2021–2024) was established. Bidirectional Mendelian randomization (MR) was employed to assess genetic associations and causal relationships between PCOS and SHBG. Molecular docking studies evaluated cryptotanshinone’s binding affinity to key proteins (COL1A1, COL4A2, COL6A2) in the PI3K/Akt pathway. GCNT2’s regulatory effects on collagen synthesis and extracellular matrix pathways. Pharmacokinetic profiling validated therapeutic viability.ResultsBidirectional MR revealed significant genetic associations (P < 0.001) and causal links between PCOS and SHBG, implicating GCNT2 as a key modulator. Cryptotanshinone exhibited strong binding affinity to PI3K/Akt signaling pathway proteins and favorable pharmacokinetic properties. Enrichment analyses highlighted GCNT2’s role in collagen biosynthesis (FDR < 0.05) and extracellular matrix regulation.DiscussionThis study identifies GCNT2 as a critical mediator of PCOS pathophysiology through SHBG modulation and collagen remodeling. Cryptotanshinone emerges as a promising therapeutic candidate, targeting PI3K/Akt signaling pathway with high specificity. These findings advance the understanding of PCOS mechanisms and provide a foundation for biomarker-driven diagnostics and precision therapeutics. Further validation in clinical trials is warranted to translate these insights into practice.